The Influence of Brand Image and Price on Pilgrims’ Decisions to Use the Services of PT AGI Tour Indonesia in Sintang Regency - Surya, Nur Afdhalia; Sumiyati, Sumiyati (Universitas KH. Abdul Chalim Mojokerto, 2025)
The increase in the number of Umrah pilgrims in Indonesia after the COVID-19 pandemic has led to stronger competition among Umrah travel agencies in providing services, determining pricing strategies, and building brand value. This situation encourages travel agencies to improve their brand image and pricing strategies in order to influence pilgrims when selecting Umrah travel services. This research aims to examine the effect of brand image and price on pilgrims’ decisions to use the services of PT AGI Tour Indonesia in Sintang Regency. This study uses a quantitative approach with primary data obtained through questionnaires distributed to 80 respondents who have used the services of PT AGI Tour Indonesia. The data were analyzed using SPSS version 26, including validity and reliability tests, classical assumption tests, multiple linear regression analysis, correlation analysis, coefficient of determination, and hypothesis testing using the t-test and F-test. The findings show that all questionnaire items related to the variables of brand image, price, and pilgrims’ decisions are valid and reliable. The classical assumption tests indicate that the data are normally distributed, linear, and free from multicollinearity. The results of multiple linear regression analysis reveal that brand image and price have positive effects on pilgrims’ decisions, with the regression equation Y = 10.889 + 0.425X₁ + 0.539X₂. The correlation coefficient (R) of 0.834 reflects a very strong relationship between brand image, price, and pilgrims’ decisions. Meanwhile, the coefficient of determination (R²) of 0.696 indicates that 69.6% of pilgrims’ decisions are influenced by brand image and price, while the remaining 30.4% is affected by other factors not examined in this study. The results of both simultaneous and partial hypothesis testing show that brand image and price significantly influence pilgrims’ decisions. Therefore, this study concludes that strengthening brand image and offering competitive pricing are important strategies for Umrah travel agencies to attract and maintain pilgrims.